Copper‐triazine‐dendrimer‐functionalized‐graphene oxide: Synthesis, characterization, and application in green synthesis of propargylamines. (24th May 2022) - Kumar, Akash; Kujur, Shelly; Kujur, Jyoti Prabha; Sharma, Richa; Pathak, Devendra Deo
Abstract: A copper‐triazine‐dendrimer‐functionalized graphene oxide (CTD‐GO) is synthesized for the first time. The structure of the dendrimer is confirmed by Fourier transform infrared (FT‐IR), Fourier transform (FT) Raman, powder X‐ray diffraction (PXRD), X‐ray photoelectron spectroscopy (XPS), energy‐dispersive X‐ray spectroscopy (EDX), field emission scanning electron microscopy (FESEM), high‐resolution transmission electron microscopy (HRTEM), elemental mapping, atomic absorption spectroscopy (AAS), and thermogravimetric analysis (TGA). The catalytic activity of the CTD‐GO is demonstrated in green synthesis of a series of propargylamine derivatives in high yields via A 3 ‐coupling of aldehyde, alkyne, and amine in water. After the reaction, the catalyst was easily recuperated from the reaction mixture and reused up to four times without any significant loss in its catalytic activity. Operational simplicity, high yields of product, use of green solvent, facile recovery and recyclability of the catalyst, and easy workup are the salient features of this procedure. Abstract : A copper‐triazine‐dendrimer‐functionalized graphene oxide (CTD‐GO) is synthesized for the first time. The CTD‐GO is characterized by FT‐IR, FT Raman, PXRD, XPS, EDX, FESEM, HRTEM, elemental mapping, AAS, and TGA. The catalytic activity of the CTD‐GO is demonstrated in green synthesis of a series of propargylamine derivatives in high yields via A 3 ‐coupling of aldehyde, alkyne, and amine in water.